The Construction of Government Regulation in Lieu of Law Number 2 of 2017 in the Perspective of National Defense - Muhammad Hamdi Karim; Mhd Halkis; Susaningtyas Nefo Handayani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The state's defense plays a central role in ensuring the continuity of society, nation, and state. Threats arising from social organizations that diverge from Pancasila and the 1945 Constitution, using the freedom of association and assembly to replace the foundational principles of Pancasila, have prompted the President to issue Government Regulation in Lieu of Law Number 2 of 2017 concerning Amendments to Law Number 17 of 2013 concerning Social Organizations (Perppu Ormas). The research method used is normative legal research, employing a qualitative approach where data is gathered in the form of descriptions focusing on Perppu Ormas. From a national defense perspective, the issuance of Perppu Ormas aims to strengthen state stability by addressing threats such as terrorism, radicalism, social conflicts, and foreign influences that potentially undermine national sovereignty. This effort also serves as a means to maintain political balance and support the positive role of social organizations in bolstering national defense.